The Influence of Calcaneal and First Ray Osteotomies on the Contact Pressures of the Ankle Joint. Issue 4 (16th October 2019) - de Cesar Netto, Cesar; Zhengyu, Gao; Abbasi, Pooyan; Smyth, Niall; Casscells, Nicholas D; Michnick, Stuart; Demetracopoulos, Constantine; Parks, Brent; Miller, Stuart
Category: Ankle, Hindfoot Introduction/Purpose: Medial displacement calcaneal osteotomies (MDCO) and first ray plantarflexion osteotomies, such as a Cotton osteotomy, are frequently used realignment procedures for hindfoot and ankle joint valgus malalignment. Multiple studies demonstrated the effects of calcaneal osteotomies on the contact pressures of the ankle joint (CPAJ), with slight medial displacement of the center of pressure and lateral unloading of the ankle joint. However, the influence of a first ray plantarflexion osteotomy on the CPAJ is yet to be determined. In this cadaveric study we compared the effects of calcaneal and first ray osteotomies in the CPAJ. Methods: Fifteen bellow-knee cadaveric specimens were dissected to expose the ankle joint and isolate the flexor and peroneal tendons. Tekscan 5033 sensors were placed in the ankle joint and held in place with cyanoacrylate. Specimens were loaded in a servohydraulic load frame. The following loads were applied to the tendons: Achilles (200 N), PTT (40 N), peroneals combined (44 N), FHL/FDL combined (35 N). Ankles were tested in an intact position, after isolated MDCO (6, 8, 10 and 12 mm), isolated Cotton osteotomies (4, 8 and 12 mm) as well as combined osteotomies (10 mm and 12 mm, respectively). Specimens were then cyclically load from 100N-700 N at a rate of 0.5 Hz for 30 cycles while CPAJ data was collected at a rate of 20 Hz. Average and maximum pressure data were extracted as well as the center of pressure (CoP) movement in the AP and ML directions. Results: There was a significant (p<0.05) and progressive decrease in respective maximum and average contact pressures of the ankle joint when comparing intact ankle (1608 and 1312kPa), calcaneal osteotomy (1291 and 1034 kPa), Cotton osteotomy (1165 and 962 kPa) and combined osteotomies (1134 and 903 kPa). Cotton osteotomy and combined osteotomies showed similar contact pressures. Regarding CoP measurements of the ankle joint, native ankle and MDCO demonstrated similar positionings in the sagittal and coronal planes. Cotton and combined osteotomies caused a significant shift of the CoP anteriorly and laterally when compared respectively to the intact/MDCO and MDCO ankles. Conclusion: The results of this study demonstrate that the Cotton osteotomy has a greater effect on the contact pressures of the ankle when compared to the MDCO. There is an overall decrease in the maximum and average pressures as well as a deviation of the center of pressure toward the anterior and lateral aspect of the ankle joint. These findings should guide surgeons when deciding between first ray and calcaneal osteotomies as realignment procedures for hindfoot and ankle valgus deformities.